(untitled) (Singaporean Journal of Business Economics and Management, 2013)
Customer displacement is an important issue in the part of communication services, (such as banking) in which, trading models for profitability depend on long-term relationships with customers. Present study is trying to investigate the role that brand can play to retain customers, as well as to promote some of their behaviors, and it per swill leads to company’s long term benefits. Brand credibility is considered as an important effective factor on customer of based brand and his/her market share. Brand credibility is a multi-characteristics term that provides brand accuracy to customers. Customer brand loyalty is a type of brand commitment that despite the potential marketing efforts of rivals to overcome the coalition between brand and customer will causes customer’s re-buying behavior.Some of the effective factors on brand loyalty in banks are: correct and good delivery, having brand credibility, having physical inventories, accurate bills, data and information that are provided to customer or customers, responding requests and questions, effective cognitive backup, satisfying, value, variation resistance, emotions, trust, brand equity.